The failure of corporate law fundamental flaws and progressive possibilities - Greenfield, Kent. (Chicago, Ill. ; London : University of Chicago Press, 2006)
Kent Greenfield hopes to return corporate law to a system in which the public has a greater say in how firms are governed. He maintains that the laws controlling firms should be much more protective of the public interest and of the corporation's various stakeholders, such as employees.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Corporation law -- United States; Corporate governance -- United States; Industrial management -- United States; Law; Politics & government; Laws of specific jurisdictions & specific areas of law; Company law